2011
DOI: 10.1080/01635581.2011.589959
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Walnut Suppressed Mammary Gland Tumorigenesis in the C(3)1 TAg Mouse

Abstract: Walnuts contain multiple ingredients that, individually, have been shown to slow cancer growth, including omega-3 fatty acids, antioxidants, and phytosterols. In previous research, consumption of walnuts has slowed the growth of implanted breast cancers. We wanted to determine whether regular walnut consumption might reduce the risk for developing cancer. Homozygous male C(3)1 TAg mice were bred with female SV129 mice consuming either the control AIN-76 diet or the walnut-containing diet. At weaning, the femal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 35 publications
0
56
0
Order By: Relevance
“…Cisplatin increased, but walnut decreased the latency to nociceptive stimuli [35]. Dietary walnut suppressed mammary gland tumorigenesis in the C(3)1 TAg mouse [90] and growth of implanted MDA-MB 231 human breast cancer cells in nude mice [91]. It has also been demonstrated that walnut reduces growth of prostate cancer [92,93] and colorectal cancer [94].…”
Section: Walnutmentioning
confidence: 99%
“…Cisplatin increased, but walnut decreased the latency to nociceptive stimuli [35]. Dietary walnut suppressed mammary gland tumorigenesis in the C(3)1 TAg mouse [90] and growth of implanted MDA-MB 231 human breast cancer cells in nude mice [91]. It has also been demonstrated that walnut reduces growth of prostate cancer [92,93] and colorectal cancer [94].…”
Section: Walnutmentioning
confidence: 99%
“…Gene expression analyses indicated that a walnut diet altered expression of multiple genes associated with proliferation and differentiation of mammary epithelial cells. Although specific bioactive components were not tested, the results of this study indicate that walnut consumption could contribute to a healthy diet for the prevention of breast cancer (Hardman et al, 2011).…”
Section: Breast Cancermentioning
confidence: 99%
“…31 Moreover, ETs and EA seem to exhibit anticancer properties in vitro and in vivo. Recent research in vitro has shown that walnut extracts have dose-dependent inhibitory effects on colon cancer cell growth 32 and it has been observed that walnuts delay the growth rate of breast cancer cells 33 and prostate cancer cells 30 implanted in mice. ET-rich herbal extracts have been shown to inhibit LNCaP cell proliferation and reduce PSA secretion.…”
Section: Introductionmentioning
confidence: 99%